DATA PROCESSING CENTER FOR RADIOSTRON PROJECT - Shatskaya, M. V.; Guirin, I. A.; Isaev, E. A.; Kostenko, V. I.; Likhachev, S. F.; Pimakov, A. S.; Seliverstov, S. I.; Fedorov, N. A. (Одеські астрономічні публікації, 2012)
Radioastron is the international project led by the Astro Space Center of Lebedev Phisical Institute. Moscow, Russian Federation. 10 m Space Radio Telescope is the main payload of Spektr-R spacecraft. It's designed by Lavochkin Association of Roscosmos Russia State Agency. The project goal is to create together with a ground based radio telescopes the huge Ground to Space interferometer with a baseline up to 350 km, to obtain images, positions and movements of various objects in the Universe with extremely high angular resolution (about 10e-6 arcsec). After successful launch on 18 July, 2012 the Radioastron missions starts systematic investigations of the Universe at broad radio frequencies range.